The energy mix dilemma in Indonesia in achieving net zero emissions by 2060 - Nasir, Muhammad Nurhalik; Bengi, Kartika Simah (Institute for Advanced Science, Social, and Sustainable Future, 2024)
Background: The global responsibility to reduce greenhouse gas emissions forces Indonesia to evaluate its energy policies and strategies. The energy mix dilemma in Indonesia arises as a consequence of rapid economic growth, rapid urbanization, and the continuously increasing energy demand. By 2060, Indonesia aims to have an energy mix dominated by renewable energy sources (RES) and to reduce its dependence on fossil fuels. The importance of reducing greenhouse gas emissions is becoming increasingly apparent, considering Indonesia is one of the countries highly vulnerable to climate change. Method: This study employs a combined approach of policy analysis and literature review. The method used in this research is an objective narrative literature review as a reference for conducting the literature study. Findings: In 2023, Indonesia is still heavily reliant on fossil fuels, primarily coal, oil, and natural gas. The Indonesian government has enacted several regulations related to energy use, including policies for the development of renewable energy. Despite efforts to reduce emissions through the application of clean technologies, the main challenge is significantly replacing fossil energy sources with renewable energy. Several inhibiting factors emerge as real challenges in the journey to achieve Net Zero Emissions. Technological and infrastructure constraints are the main obstacles. The strategic importance of sustainable economic growth is a central point in this dilemma. However, the transition to net zero emissions often requires structural adjustments that can impact the economy. Conclusion: The process of transitioning to renewable energy must be carefully implemented to avoid the risk of supply instability. The alignment between economic growth, energy security, and emission reduction is key to designing effective and sustainable policies. Novelty/Originality of this Study: This study provides a comprehensive examination of Indonesia's energy mix dilemma in the context of achieving net zero emissions by 2060, specifically highlighting the intricate balance between sustainable economic growth, energy security, and global climate commitments. By adopting a holistic approach that involves the government, private sector, and societal participation, the research offers innovative policy recommendations for transitioning from non-renewable to renewable energy sources while addressing socio-economic challenges.